TiO2 photocatalytic inactivation under simulated solar light of bacterial consortia in domestic wastewaters previously treated by UASB, Duckweed and Facultative ponds - Rengifo Herrera, Julian Andres (2010)
In this work, TiO2 photocatalysis was used to disinfect domestic wastewaters previously treated by different biological treatment systems: Upward-flow Anaerobic Sludge Blanket (UASB), facultative pond, and duckweed pond. The microorganisms monitored were E. coli, total coliforms, Shigella species, and Salmonella species. Photocatalytic experiments were carried out using two light sources:a solar simulator (UV intensity: 68-70 W m-2) and black-light lamps (BLL UV intensity: 17-20 W m-2). Samples were taken after each treatment stage. Results indicate that bacterial photocatalytic inactivation is affected by characteristics of the effluent, including turbidity, concentration of organic matter, and bacterial concentration, which depend of the type of biological pretreatment previously used.